Estrategia de fijación de precios en la industria hotelera: El caso del hotel Tryp Atocha Madrid; Pricing strategy in the hotel industry - Elena Calvo; Javier Tapia; Pablo Albisu (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2022)
– Determining the daily accommodation price that customers pay per night is essential for hotel managers. The price changes for different reasons: demand, competition price, prices for groups, holidays or days with a major event in the city, and customer satisfaction. In this research, we evaluate the influential variables in the price per room that is charged to the clients of a hotel in Madrid. Six-month information provided by the Melia Hotels International Company has been used. The results describe that an increase in BAR, competitor's price and individual-group rates increases the price while an event decreases it.
Keywords: D40; L83; 330; price formation; hotel occupancy; BAR; ADR; Madrid